Perceptions of Physical Education teachers from a metropolitan region of southern Brazil about the repercussions of the COVID-19 on their pedagogical practices - Beatriz Freitas da Cunha; Samara Escobar Martins; Maria Eduarda Tomaz Luiz; Vitória Matos Garibaldi; Alcyane Marinho (Universidad de Costa Rica, 2023)
The COVID-19 pandemic has had an impact around the world, impacting various sectors of society, including education and consequently school physical education. In this way, we sought to investigate, through a descriptive-exploratory field research, with a qualitative approach to the data, the perceptions of Physical Education teachers from a metropolitan region of southern Brazil about the repercussions of the pandemic on their pedagogical practices. To this end, sixteen teachers participated in this study, nine from the public school system and seven from the private network, through semi-structured interviews, online, during the months of June and July 2021. The data, which were organized through the NVivo-12 software and analyzed by the content analysis technique, point to difficulties, facilities and learning resulting from experiences during the pandemic. Aspects of emergency remote teaching, the application of security protocols in physical education classes and the potential of physical education for students in the current and future context were addressed. From these findings it was possible to verify that these teachers needed, more than ever, to develop their adaptive skills. This is because this study demonstrated that Physical Education classes were the only time when children are out of the classroom, being perceived as a moment of liberation, after experiencing the restrictions imposed by the pandemic, considering that these teachers provide feelings of lightness, joy, and manifestation of expressions. Thus, the findings of this study can contribute to reflections and overcoming of future challenges related to the teaching of School Physical Education. For this, future research is needed to verify how these consequences are reverberating over time.